A High Efficient and Real Time Data Aggregation Scheme for WSNs. (28th June 2015) - Du, Tao; Qu, Zhe; Guo, Qingbei; Qu, Shouning
Data aggregation is an important method of improving transmitting efficiency of WSNs, but existing researches have some disadvantages as follows: several periods delay will be generated when filtering messages; the reduplicated messages filtering ratio is low; complex calculations need to be executed; and extra hardware should be added to obtain high performance. To resolve these problems, this paper proposes a real time and high efficient data aggregation scheme (dynamical message list based data aggregation, DMLDA) based on clustering routing algorithm. DMLDA includes three procedures: activating nodes, clustering nodes, and filtering messages. In filtering procedure, a special data structure named dynamic list will be established in every filtering node; it is designed to store messages transmitted by filtering node, and, comparing current message with list's items, the message's redundancy can be judged without any delay. To improve the filtering efficiency, the message list can be adjusted dynamically. The three procedures of data aggregation are all introduced, and the filtering method is designed in detail in this paper. At last, a series of experiments are simulated to prove our scheme's performance, and the advantages are analyzed in theory.